Effects of Soil Organic Matter, Total Nitrogen and Texture on Nitrogen Mineralization Process - Najmadeen, Hastyar H (Al-Nahrain Journal of Science, 2011)
The objectives of this study were to 1. Determine soil texture, microbial com0munities, chemical and physical properties of soils collected from nine different localities of Sulaimani governorate; 2. Measuring the rates of nitrogen mineralization of plant residues and it's correlation with tested parameters. After analysis, soils were classified into six textures (sandy loam, loamy sand, silty loam, silty clay loam, loam and clay loam). Statistical analysis of variance indicated there were no significant differences among soil textures in fungal counts (ranging from 4.09–4.49 log of CFU per 1 g dry soil) whereas total bacteria showed significantly higher in clay loam and silty clay loam in compare to other soil textures (ranging from 6.07–8.77 log of CFU per 1 g dry soil), soil chemical analysis showed that the soil organic matters and total nitrogen contents are strongly correlated with each other (r2=0.96, p≤0.001), and both parameters indicated positive correlation with the major microbial groups (r2=0.798, r2=0.772, p≤0.001) respectively, whereas they are negatively correlated with mineralization rate (r2=-0.379, r2=-0.338, p≤0.001) respectively; finally the effects of soil texture on N-mineralization showed that this process tends to be greater in coarse-textured soils than fine textured soils.